Kinetic expression for the isothermal crystallization of poly(3‐hydroxybutyrate)–11%poly(3‐hydroxyvalerate) - Cyras, Viviana Paola (2004)
The use of polyhydroxyalkanoates as a biodegradable semicrystalline polymer is currently increasing. The prediction of crystallinity profiles produced in part with this polymer requires the knowledge of the kinetic expression. In the present article, a kinetic expression of the isothermal melt crystallization of poly(3-hydroxybutyrate)-11%poly(3-hydroxyvalerate) [P(HB-co-11%HV)] was studied in two temperature ranges, close to the melting point and close to the glass transition. Melting behavior and mo lecular mobility of the amorphous phase were analyzed as a function of crystallization temperatures by performing calorimetric experiments. The Avrami equation was used and the activation energy of the crystal nucleation and growth were obtained.